Boron-containing polycyclic aromatic compounds and applications thereof
Patent Information
- Application Number
- CN202310821980.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-05
- Publication Date
- 2026-10-13
- Estimated Expiration
- 2043-07-05
AI Technical Summary
但是这种给-受体材料激发态振动迟豫明显,具有较大的Stokes位移,导致发射光谱较宽,一般半峰宽大于60nm
[0030]本发明为了减小发光材料的斯托克斯频移(Stokes shift),进一步提高有机电致发光材料的色纯度、效率等光电性能,尤其是提高蓝光材料的发光性能,提供一种新型含硼有机发光材料,通过咔唑并噁唑或咔唑并咪唑或咔唑并吡咯衍生物和硼原子构筑多环芳香族化合物,利用硼原子、氮原子、氧原子、硫原子、硒原子之间的多重共振效应,获得高性能、窄光谱发射、结构多样的MR-TADF材料。
Smart Images

Figure CN116854719B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of organic electroluminescent materials technology, and relates to boron-containing polycyclic aromatic compounds and their applications, specifically to a class of boron-containing intercalated polycyclic conjugated aromatic compounds and their applications in luminescent materials. Background Technology
[0002] Organic light-emitting devices (OLEDs) possess characteristics such as flexibility, ultra-light weight, ultra-thinness, low energy consumption, wide viewing angle, active emission, and fast response speed. They hold an important position in the field of display technology today and in the future, and are considered the most promising next-generation flat panel display and solid-state lighting technology. OLEDs typically consist of an ITO anode, a hole injection layer (HIL), a hole transport layer (HTL), an emissive layer (EML), a hole blocking layer (HBL), an electron transport layer (ETL), an electron injection layer (EIL), and a cathode. Excitons are formed by the combination of holes and electrons injected into the organic film by the positive and negative electrodes. When the excitons return from the excited state to the stable ground state, they release energy in the form of light, thus emitting light. Due to the limitations imposed by spin quantum statistics, traditional fluorescent materials can only utilize singlet excitons, which account for 25% of all excitons, during electroluminescence. The remaining 75% of triplet excitons are deactivated through non-radiative transitions, resulting in a maximum quantum efficiency (IQE) of 25%. Phosphorescent metal complexes, however, can utilize both singlet and triplet excitons simultaneously due to the heavy atom effect, achieving a quantum efficiency of 100%. However, phosphorescent metal complexes are prohibitively expensive.
[0003] Thermally activated delayed fluorescence (TADF) materials are the third generation of organic electroluminescent materials, following traditional fluorescence and phosphorescence. These materials generally possess a small singlet-triplet energy level difference (ΔEst), emitting light by converting triplet excitons into singlet excitons through a system inversion (RISC) process, achieving a theoretical internal quantum efficiency of 100%. However, these materials typically contain donor-acceptor units, effectively separating the highest occupied orbital (HOMO) and lowest unoccupied orbital (LUMO), resulting in a small ΔEst. However, these donor-acceptor materials exhibit significant vibrational lag in the excited state, with a large Stokes shift, leading to a broad emission spectrum, typically with a full width at half maximum (FWHM) greater than 60 nm. For OLED displays, while optical techniques such as filters or microcavity effects can be used to narrow the spectrum and achieve high color purity emission spectra, these methods significantly increase power consumption and product cost, and also sacrifice actual luminous efficiency, resulting in energy waste. The key to OLED display technology's ability to exhibit high color purity and a wide color gamut lies in the organic electroluminescent materials. Therefore, developing organic electroluminescent materials with narrow-band emission characteristics to improve the color purity of display devices is of paramount importance. Summary of the Invention
[0004] The purpose of this invention is to provide an organic electroluminescent material with narrow-band emission characteristics to improve the color purity of display devices.
[0005] For the purposes described above, this application addresses this need in the field by providing boron-containing polycyclic aromatic compounds and their applications.
[0006] On the one hand, the present invention relates to boron-containing polycyclic aromatic compounds, the structure of which is shown in formula (I):
[0007]
[0008] Where X1 is an O atom or NAr1, X2 is an N atom or a C atom, any one of X3 to X6 is an N atom or a C atom, and Y1 is one of O, NAr2, S, Se, and C;
[0009] Ar1 is aryl or heteroaryl, Ar2 is aryl or heteroaryl, Ar3 is hydrogen atom, deuterium atom, alkyl, substituted or unsubstituted aryl, heteroaryl, or amino, and Ar4 is hydrogen atom, deuterium atom, alkyl, or aryl; preferably, when Ar4 is aryl, Ar4 is phenyl.
[0010] On the other hand, the present invention relates to boron-containing polycyclic aromatic compounds, the structure of which is shown in formula (II):
[0011]
[0012] Where X1 is an O atom or NAr1, X2 is an N atom or a C atom, and X3 to X... 10 Any one of them can be represented as an N atom or a C atom, and Y2 can be one of O, NAr2, S, Se, and C;
[0013] Ar1 is aryl or heteroaryl, Ar2 is aryl or heteroaryl, and Ar3 is hydrogen atom, deuterium atom, alkyl, substituted or unsubstituted aryl or heteroaryl.
[0014] On the other hand, the present invention relates to boron-containing polycyclic aromatic compounds, the structure of which is shown in formula (Ⅲ):
[0015]
[0016] Where X1 is an O atom or NAr1, and X2 is an N atom or a C atom;
[0017] Ar3 is a hydrogen atom, a deuterium atom, an alkyl group, a substituted or unsubstituted aryl group, or a heteroaryl group; Ar4 is a hydrogen atom, a deuterium atom, an alkyl group, or an aryl group; preferably, when Ar4 is an aryl group, Ar4 is a phenyl group.
[0018] For example, the present invention provides a specific structure of the above-mentioned boron-containing polycyclic aromatic compounds, including:
[0019]
[0020]
[0021]
[0022]
[0023]
[0024]
[0025] Furthermore, in the boron-containing polycyclic aromatic compounds provided by the present invention, one or more of the hydrogen atoms bonded to C are replaced by deuterium atoms.
[0026] On the other hand, the present invention relates to the application of the above-mentioned boron-containing polycyclic aromatic compounds in the fabrication of organic electroluminescent devices.
[0027] On the other hand, the present invention relates to an organic electroluminescent device, comprising a light-emitting layer, wherein the raw materials for preparing the light-emitting layer include at least one of the above-mentioned boron-containing polycyclic aromatic compounds.
[0028] As materials for organic light-emitting devices (OLEDs), various materials have been developed in the industry. In particular, thermally active delayed fluorescence materials (TADF) have played a significant role in improving device efficiency. However, due to the effective separation of the highest occupied orbital (HOMO) and lowest unoccupied orbital (LUMO) in TADF materials, intramolecular charge transfer mainly occurs under the action of an electric field, resulting in a large Stokes shift, a wide full width at half maximum (FWHM) of the emission spectrum, and a deterioration in color purity.
[0029] Compared with the prior art, the present invention has the following beneficial effects or advantages:
[0030] To reduce the Stokes shift of luminescent materials and further improve the photoelectric properties of organic electroluminescent materials, such as color purity and efficiency, especially the luminescence performance of blue light materials, this invention provides a novel boron-containing organic luminescent material. This material constructs polycyclic aromatic compounds using carbazole-oxazole, carbazole-imidazolium, or carbazole-pyrrole derivatives and boron atoms. Utilizing the multiple resonance effects among boron, nitrogen, oxygen, sulfur, and selenium atoms, high-performance, narrow-spectrum emission, and structurally diverse MR-TADF materials are obtained. Attached Figure Description
[0031] Figure 1 This is a schematic diagram of the structure of an organic electroluminescent element provided in an embodiment of the present invention.
[0032] Explanation of reference numerals in the attached figures: 1 is the substrate, 2 is the anode layer, 3 is the hole injection layer, 4 is the first hole transport layer, 5 is the second hole transport layer, 6 is the light-emitting layer, 7 is the hole blocking layer, 8 is the electron transport layer, 9 is the electron injection layer, and 10 is the cathode layer. Detailed Implementation
[0033] The technical solution of the present invention will be described below with reference to the embodiments. However, the present invention is not limited to the following embodiments.
[0034] To enable those skilled in the art to better understand and implement the technical solutions of the present invention, the present invention will be further described below in conjunction with specific embodiments and accompanying drawings. However, the embodiments described are not intended to limit the present invention.
[0035] Unless otherwise specified, the experimental and detection methods described in the following embodiments are conventional methods; unless otherwise specified, the reagents and materials are commercially available.
[0036] Synthesis Examples
[0037] This synthetic example provides the preparation of compounds 3, 8, 16, 23, 50, 76, 102, and 106. Other compounds provided in this application can be obtained by referring to the synthetic methods described below.
[0038] (1) Synthesis of Compound 3
[0039]
[0040] Under argon protection, 1,3-dibromo-2-chloro-5-iodobenzene (80.0 g, 201.9 mmol), 3,6-di-tert-butylcarbazole (56.4 g, 201.9 mmol), potassium carbonate (38.8 g, 403.8 mmol), cuprous bromide (2.9 g, 20.2 mmol), 1,10-o-phenanthroline (7.3 g, 40.4 mmol), and toluene (1 L) were added sequentially to a reaction flask, and the mixture was heated to reflux for 8 h. After the reaction was complete, the system was cooled to room temperature. The mixture was washed with water until neutral, dried over anhydrous sodium sulfate, passed through a silica gel column, concentrated by column chromatography, and recrystallized from the concentrate with a suitable amount of toluene / ethanol to give 84.3 g of white solid A-1, with a yield of 76.2%.
[0041] Under nitrogen protection, intermediate A-1 (80.0 g, 146.0 mmol), di(4-tert-butylphenyl)amine (41.1 g, 146.0 mmol), potassium carbonate (40.3 g, 292.1 mmol), cuprous bromide (2.1 g, 14.6 mmol), 1,10-phenanthroline (5.3 g, 29.2 mmol), and toluene (1 L) were added sequentially to a reaction flask, and the mixture was heated to reflux for 8 h. After the reaction was complete, the system was cooled to room temperature. The mixture was washed with water until neutral, dried over anhydrous sodium sulfate, passed through a silica gel column, concentrated by column chromatography, and recrystallized from the concentrate with a suitable amount of toluene / ethanol to give 78.6 g of compound A-2 as a white solid, with a yield of 71.9%.
[0042] Under argon protection, intermediate A-2 (75.0 g, 100.2 mmol), 10H-oxazolo[4,5-a]carbazole (21.9 g, 105.2 mmol), sodium tert-butoxide (14.4 g, 150.3 mmol), Pd2(dba)3 (0.9 g, 1.0 mmol), XantPhos (1.1 g, 2.0 mmol), and toluene (1 L) were added sequentially to a reaction flask, and the mixture was heated to reflux for 8 h. After the reaction was complete, the system was cooled to room temperature. The mixture was washed with water until neutral, dried over anhydrous sodium sulfate, passed through a silica gel column, concentrated by column chromatography, and recrystallized from the concentrate with a suitable amount of toluene / ethanol to give 59.0 g of white solid A-3, with a yield of 67.3%.
[0043] Under nitrogen protection, intermediate A-3 (65.0 g, 74.2 mmol) and xylene (300 mL) were added sequentially to a reaction flask, and the system was cooled to -40 °C. Tert-butyllithium (69.6 mL, 111.4 mmol, 1.6 M) was then added dropwise. After the addition was complete, the temperature was raised to 0 °C and stirring was continued for 2 h. Boron tribromide (46.5 g, 185.5 mmol) was then added dropwise between -40 °C and -30 °C. After the addition was complete, the reaction was continued at 50 °C for 2 h. The system was then cooled to 0 °C, and DIEA (24.0 g, 185.5 mmol) was added. After the addition was complete, the temperature was gradually raised to 120 °C, and the reaction was continued at this temperature for 8 h. After the reaction was complete, the solvent was removed by vacuum distillation. The crude product was slurried with ethanol and recrystallized from toluene / ethanol to give 20.0 g of a pale yellow solid, with a yield of 31.8%.
[0044] The mass spectrometry results of the obtained sample were: HR-MS (APCI): m / z 849.4625 [M+H] + Calculated values of C59H57OBN4 (%): C, 83.47%; H, 6.77%; O, 1.88%; N, 6.60%; Measured values: C, 83.49%; H, 6.78%; O, 1.86%; N, 6.61%.
[0045] (2) Synthesis of Compound 8
[0046]
[0047] Under argon protection, 1,3-dibromo-2-chloro-5-iodobenzene (80.0 g, 201.9 mmol), deuterated phenylboronic acid (23.6 g, 201.9 mmol), potassium carbonate (55.7 g, 403.8 mmol), tetrabutylammonium bromide (1.9 g, 6.0 mmol), tetra(triphenylphosphine)palladium (3.5 g, 3.0 mmol), toluene (800 mL), ethanol (200 mL), and water (200 mL) were added sequentially to a reaction flask, and the mixture was heated to reflux for 8 h. After the reaction was complete, the system was cooled to room temperature. The solution was washed with water until neutral, dried over anhydrous sodium sulfate, passed through a silica gel column, concentrated by column chromatography, and recrystallized with a suitable amount of toluene / ethanol to give 56.7 g of white solid B-1, with a yield of 82.3%.
[0048] Under nitrogen protection, B-1 (55.0 g, 161.1 mmol), B-2 (45.6 g, 161.1 mmol), potassium carbonate (44.5 g, 322.2 mmol), cuprous bromide (2.3 g, 16.1 mmol), 1,10-phenanthroline (5.8 g, 32.2 mmol), and toluene (800 mL) were added sequentially to a reaction flask, and the mixture was heated to reflux for 8 h. After the reaction was complete, the system was cooled to room temperature. The mixture was washed with water until neutral, dried over anhydrous sodium sulfate, passed through a silica gel column, concentrated by column chromatography, and recrystallized from the concentrate with a suitable amount of toluene / ethanol to give 57.7 g of white solid B-3, with a yield of 65.9%.
[0049] Synthesis of intermediate B-4: Following the synthetic method of compound A-3, compound A-2 was replaced with compound B-3, with a yield of 63.3%.
[0050] Synthesis of compound 8: Following the synthetic method of compound 3, compound A-3 was replaced with compound B-4, yield 27.1%.
[0051] The mass spectrometry results of the obtained sample were: HR-MS (APCI): m / z 645.2622 [M+H] + Calculated values of C43H31OBN5 (%): C, 80.13%; H, 4.85%; O, 2.48%; N, 10.87%; Measured values: C, 80.12%; H, 4.85%; O, 2.49%; N, 10.89%.
[0052] (3) Synthesis of Compound 16
[0053]
[0054] Under argon protection, compound C-1 (150.0 g, 383.2 mmol), triphenylphosphine (201.0 g, 766.4 mmol), and xylene (1.5 L) were added sequentially to a reaction flask, and the mixture was heated to reflux for 8 h. After the reaction was complete, the system was cooled to room temperature, ethanol was added, and stirring was performed to precipitate a solid. The solid was filtered, the filter cake was dissolved in toluene, and then passed through a silica gel column. The column chromatography solution was concentrated, and the solid was recrystallized with an appropriate amount of toluene / ethanol to give 51.8 g of white solid C-2, with a yield of 37.6%.
[0055] Under argon protection, 1,3-dibromo-2-chloro-5-iodobenzene (50.0 g, 153.2 mmol), compound C-2 (115.6 g, 321.6 mmol), sodium tert-butoxide (44.1 g, 459.6 mmol), Pd2(dba)3 (1.4 g, 1.5 mmol), XantPhos (1.8 g, 3.1 mmol), and toluene (1 L) were added sequentially to a reaction flask, and the mixture was heated to reflux for 8 h. After the reaction was complete, the system was cooled to room temperature. The mixture was washed with water until neutral, dried over anhydrous sodium sulfate, passed through a silica gel column, concentrated by column chromatography, and recrystallized from the concentrate with a suitable amount of toluene / ethanol to give 83.2 g of white solid C-3, with a yield of 61.5%.
[0056] Synthesis of compound 16: Following the synthetic method of compound 3, compound A-3 was replaced with compound C-3, yield 28.5%.
[0057] The mass spectrometry results of the obtained sample were: HR-MS (APCI): m / z 857.3486 [M+H] + Calculated values of C60H41BN6 (%): C, 84.11%; H, 4.82%; N, 9.81%; Measured values: C, 84.08%; H, 4.81%; N, 9.82%.
[0058] (4) Synthesis of Compound 23
[0059]
[0060] Under argon protection, 1-bromo-2-chloro-3,5-diiodobenzene (50.0 g, 112.8 mmol), 3,6-di-tert-butylcarbazole (66.2 g, 236.9 mmol), potassium carbonate (46.7 g, 338.4 mmol), cuprous bromide (3.2 g, 22.6 mmol), 1,10-phenanthroline (8.1 g, 45.2 mmol), and toluene (1 L) were added sequentially to a reaction flask, and the mixture was heated to reflux for 8 h. After the reaction was complete, the system was cooled to room temperature. The mixture was washed with water until neutral, dried over anhydrous sodium sulfate, passed through a silica gel column, concentrated by column chromatography, and recrystallized from the concentrate with a suitable amount of toluene / ethanol to give 61.6 g of white solid D-1, with a yield of 73.2%.
[0061] Synthesis of intermediate D-2: Following the synthesis method of compound A-3, compound A-2 was replaced with compound D-1, with a yield of 68.1%.
[0062] Synthesis of compound 23: Following the synthetic method of compound 3, compound A-3 was replaced with compound D-2, yield 32.3%.
[0063] The mass spectrometry results of the obtained sample were: HR-MS (APCI): m / z 847.4469 [M+H] + Calculated values of C59H55OBN4 (%): C, 83.67%; H, 6.55%; O, 1.89%; N, 6.62%; Measured values: C, 83.69%; H, 6.63%; O, 1.90%; N, 6.60%.
[0064] (5) Synthesis of Compound 50
[0065]
[0066] Synthesis of intermediate E-1:
[0067] Under argon protection, 4-tert-butyldeuterium bromobenzene (50.0 g, 239.1 mmol), pinacol diborate (60.7 g, 239.1 mmol), potassium acetate (46.9 g, 478.2 mmol), bis(triphenylphosphine) palladium dichloride (1.7 g, 2.4 mmol), and toluene (1 L) were added sequentially to a reaction flask, and the mixture was heated to 80 °C for 8 h. After the reaction was complete, the system was cooled to room temperature. The mixture was washed with water until neutral, dehydrated with anhydrous sodium sulfate, and purified by silica gel column chromatography to give 51.4 g of white solid E-1, with a yield of 83.9%.
[0068] Synthesis of intermediate E-2: Following the synthesis method of compound B-1, deuterated phenylboronic acid was replaced with 4-tert-butyldeuterated phenylboronic acid pinacol ester, with a yield of 79.6%.
[0069] Synthesis of intermediate E-3:
[0070] Under argon protection, intermediate E-2 (50.0 g, 125.5 mmol), 3-phenyl-10H-pyrrolo[3,2-a]carbazole (37.1 g, 125.5 mmol), sodium tert-butoxide (24.1 g, 251.0 mmol), Pd2(dba)3 (1.2 g, 1.3 mmol), XantPhos (1.4 g, 2.5 mmol), and toluene (800 mL) were added sequentially to a reaction flask, and the mixture was heated to reflux for 8 h. After the reaction was complete, the system was cooled to room temperature. The mixture was washed with water until neutral, dried over anhydrous sodium sulfate, passed through a silica gel column, concentrated by column chromatography, and recrystallized from the concentrate with a suitable amount of toluene / ethanol to give 49.5 g of white solid E-3, with a yield of 64.3%.
[0071] Synthesis of intermediate E-4: Following the synthesis method of compound A-3, 10H-oxazolo[4,5-a]carbazole was replaced with 3-phenyl-10H-pyrrolo[3,2-a]carbazole, with a yield of 65.6%.
[0072] Synthesis of compound 50: Following the synthesis method of compound 3, compound A-3 was replaced with compound E-4, yield 27.7%.
[0073] The mass spectrometry results of the obtained sample were: HR-MS (APCI): m / z 788.3734 [M+H] + Calculated values of C56H46OBN3 (%): C, 85.38%; H, 5.89%; O, 2.03%; N, 5.33%; Measured values: C, 85.36%; H, 5.89%; O, 2.05%; N, 5.32%.
[0074] (6) Synthesis of Compound 76
[0075]
[0076] Under nitrogen protection, 1-bromo-2-chloro-3-fluoro-5-iodobenzene (60.0 g, 178.9 mmol), di(4-tert-butylphenyl)amine (50.4 g, 178.9 mmol), potassium carbonate (37.0 g, 268.4 mmol), cuprous bromide (2.6 g, 17.9 mmol), 1,10-phenanthroline (3.2 g, 17.9 mmol), and toluene (1 L) were added sequentially to a reaction flask, and the mixture was heated to reflux for 8 h. After the reaction was complete, the system was cooled to room temperature. The mixture was washed with water until neutral, dried over anhydrous sodium sulfate, passed through a silica gel column, concentrated by column chromatography, and recrystallized from the concentrate with a suitable amount of toluene / ethanol to give 71.6 g of white solid F-1, with a yield of 81.9%.
[0077] Synthesis of intermediate F-2: Compound F-1 (60.00 g, 122.7 mmol), 4-tert-butylphenol (18.4 g, 122.7 mmol), cesium carbonate (48.0 g, 147.3 mmol), and DMF (800 mL) were added sequentially to a reaction flask, and the mixture was heated under reflux for 6 h. After the reaction was complete, the system was cooled to room temperature. The mixture was filtered, and a large amount of water was added, resulting in the formation of a white precipitate, which was collected by vacuum filtration. The precipitate was washed successively with water and ethanol. Finally, the resulting filter cake was dissolved in an appropriate amount of toluene / ethanol and recrystallized to give 66.2 g of a white solid, with a yield of 87.2%.
[0078] Synthesis of intermediate F-3: Following the synthesis method of compound A-3, compound A-2 was replaced with compound F-2, with a yield of 75.9%.
[0079] Synthesis of compound 76: Following the synthetic method of compound 3, compound A-3 was replaced with compound F-3, yield 23.8%.
[0080] The mass spectrometry results of the obtained sample were: HR-MS (APCI): m / z 720.3683 [M+H]+ Calculated values of C49H46O2BN3 (%): C, 81.77%; H, 6.44%; O, 4.45%; N, 5.84%; Measured values: C, 81.78%; H, 6.46%; O, 4.44%; N, 5.82%.
[0081] (7) Synthesis of Compound 102
[0082]
[0083] Synthesis of intermediate G-1: Following the synthesis method of compound B-1, deuterated phenylboronic acid was replaced with deuterated 9-phenylcarbazole-3-boronic acid, with a yield of 72.5%.
[0084] Synthesis of intermediate G-2:
[0085] Under argon protection, intermediate G-1 (40.0 g, 80.1 mmol), 10H-oxazolo[4,5-a]carbazole (36.7 g, 176.2 mmol), sodium tert-butoxide (30.7 g, 32.0 mmol), Pd2(dba)3 (1.5 g, 1.6 mmol), XantPhos (1.8 g, 3.2 mmol), and toluene (1 L) were added sequentially to a reaction flask, and the mixture was heated to reflux for 8 h. After the reaction was complete, the system was cooled to room temperature. The mixture was washed with water until neutral, dried over anhydrous sodium sulfate, passed through a silica gel column, concentrated by column chromatography, and recrystallized from the concentrate with a suitable amount of toluene / ethanol to give 38.0 g of white solid G-2, with a yield of 62.9%.
[0086] Synthesis of compound 102: Following the synthesis method of compound 3, compound A-3 was replaced with compound G-2, yield 29.3%.
[0087] The mass spectrometry results of the obtained sample were: HR-MS (APCI): m / z 728.1241 [M+H] + Calculated values of C50H14O2BN5 (%): C, 82.55%; H, 1.94%; O, 4.40%; N, 9.63%; Measured values: C, 82.53%; H, 1.94%; O, 4.38%; N, 9.60%.
[0088] (8) Synthesis of Compound 106
[0089]
[0090] Under argon protection, intermediate A-1 (40.0 g, 73.0 mmol), 3-phenyl-10H-pyrrolo[3,2-a]carbazole (45.4 g, 160.6 mmol), sodium tert-butoxide (28.1 g, 292.1 mmol), Pd2(dba)3 (1.3 g, 1.4 mmol), XantPhos (1.6 g, 2.8 mmol), and toluene (1 L) were added sequentially to a reaction flask, and the mixture was heated to reflux for 8 h. After the reaction was complete, the system was cooled to room temperature. The mixture was washed with water until neutral, dried over anhydrous sodium sulfate, passed through a silica gel column, concentrated by column chromatography, and recrystallized from the concentrate with a suitable amount of toluene / ethanol to give 45.7 g of white solid H-1, with a yield of 65.9%.
[0091] Synthesis of compound 106: Following the synthetic method of compound 3, compound A-3 was replaced with compound H-1, yield 24.9%.
[0092] The mass spectrometry results of the obtained sample were: HR-MS (APCI): m / z 924.4159 [M+H] + Calculated values of C66H50BN5 (%): C, 85.80%; H, 5.45%; N, 7.58%; Measured values: C, 85.81%; H, 5.47%; N, 7.59%.
[0093] Device Example 1
[0094] This embodiment provides the energy level simulation calculation of the compound provided by the present invention and its application effect in organic electroluminescent devices.
[0095] This embodiment provides an organic electroluminescent device, the structure of which is as follows: Figure 1 As shown, the substrate 1, anode layer 2, hole injection layer 3, first hole transport layer 4, second hole transport layer 5, light-emitting layer 6, hole blocking layer 7, electron transport layer 8, electron injection layer 9, and cathode layer 10 are stacked sequentially.
[0096] Specifically, the anode layer 2 is made of indium tin oxide (ITO) with a high work function; the hole injection layer 3 is made of HATCN with a thickness of 5 nm; the first hole transport layer 4 is made of HT1 with a thickness of 60 nm; the second hole transport layer 5 is made of HT2 with a thickness of 15 nm; the light-emitting layer 6 uses mCBP as the host material and compound 3 as the light-emitting material, with a doping mass ratio of 3% and a thickness of 30 nm; the hole blocking layer 7 is made of TPBi with a thickness of 10 nm; the electron transport layer 8 is made of ET-1 with a thickness of 35 nm; the electron injection layer 9 is made of Liq with a thickness of 2 nm; and the cathode layer is made of Al with a thickness of 100 nm.
[0097] The basic material structures used in each functional layer of the device are as follows:
[0098]
[0099]
[0100] The specific fabrication steps of the above-mentioned organic electroluminescent device are as follows:
[0101] 1) Clean the ITO anode on the transparent glass or plastic substrate by ultrasonic cleaning with deionized water, acetone and ethanol for 20 minutes each, and then perform plasma treatment in an oxygen atmosphere for 5 minutes.
[0102] 2) On the ITO anode layer, a hole injection layer material HATCN with a thickness of 5nm is deposited by vacuum evaporation. This layer serves as the hole injection layer.
[0103] 3) Hole transport material HT1 with a thickness of 60nm is deposited on the hole injection layer by vacuum evaporation. This layer serves as the first hole transport layer.
[0104] 4) Hole transport material HT2 with a thickness of 15nm is deposited on the first hole transport layer HT1 by vacuum evaporation. This layer serves as the second hole transport layer.
[0105] 5) On the second hole transport layer, a light-emitting layer is co-deposited by vacuum evaporation, using mCPB as the host material and compound 3 as the light-emitting material, with a doping mass ratio of 3% and a thickness of 30nm;
[0106] 6) On the light-emitting layer, hole-blocking material TPBi with a thickness of 10nm is deposited by vacuum evaporation. This layer serves as a hole-blocking layer.
[0107] 7) Electron transport material ET-1 with a thickness of 35nm is deposited on the hole blocking layer by vacuum evaporation. This layer serves as the electron transport layer.
[0108] 8) On the electron transport layer, the electron injection material Liq is deposited by vacuum evaporation with a thickness of 2nm. This layer serves as the electron injection layer.
[0109] 9) On the electron injection layer, cathode Al is deposited by vacuum evaporation with a thickness of 100 nm. This layer is used as the cathode conductive electrode.
[0110] Device Examples 2 to Device Examples 8
[0111] The implementation process is the same as in Device Example 1, except that compound 3 is replaced with another developed compound as the luminescent material.
[0112] Comparative Example 1
[0113] The implementation process is the same as in Device Example 1, except that BD-1 is used as the luminescent material to replace compound 3.
[0114] The T1 energy and HOMO and LUMO energy levels of some of the compounds provided in the above embodiments and existing materials were calculated, and the results are shown in Table 1:
[0115] Table 1. HOMO, LUMO, and triplet energy values of the compounds of this invention.
[0116]
[0117]
[0118] Note: The highest molecular occupied orbital (HOMO) and the lowest molecular unoccupied orbital (LUMO), and the T1 value are data calculated by simulation software.
[0119] As shown in Table 1, the compounds disclosed in this invention have suitable HOMO / LUMO, and these compounds are suitable for use as luminescent materials.
[0120] The components of the different devices prepared in Examples 1-8 and Comparative Example 1 of the present invention are shown in Table 2.
[0121] Table 2. Comparison of the constituent components of organic electroluminescent devices in various device embodiments.
[0122]
[0123]
[0124] The cathodes and anodes of each group of organic electroluminescent devices were connected using a known driving circuit. The voltage-efficiency-brightness relationship of the OLED devices was tested using a Keithley 2400 power supply and a PR670 photometer according to standard methods. The test results are shown in Table 3.
[0125] Table 3. Performance results of organic electroluminescent devices in each group
[0126]
[0127] As shown in Table 3, the compounds provided by this invention exhibit excellent performance when used as luminescent materials in OLED devices. The structure of BD-1 demonstrates that even aromatic compounds with similar constituent elements to the core structure of the compounds provided by this invention show significant differences in their performance as luminescent materials due to their structural differences. For example, compound 23 in device example 4, compared to BD-1 in comparative example 1, exhibits a 3.4% higher external quantum efficiency, a narrower emission spectrum, and higher color purity as a blue light material. Device example 7 shows that the hydrogen atoms partially bonded to carbon atoms in the compounds provided by this invention are deuterated, resulting in excellent performance as a luminescent material. Compound 102 shows a 3.7% higher luminous efficiency compared to BD-1 in comparative example 1. Therefore, using the compounds of this invention as luminescent materials, compared to existing materials, results in superior photoelectric properties such as luminous efficiency and color purity in OLED devices, demonstrating significant application value and promising industrialization prospects.
[0128] In summary, this invention provides a class of boron-containing polycyclic conjugated aromatic compounds. These compounds, modified with specific groups, possess suitable frontier orbital energy levels. The innovative series of compounds exhibit excellent performance as luminescent materials in organic light-emitting diode (OLED) devices.
[0129] As described above, the present invention can be well implemented. The above embodiments are merely descriptions of preferred embodiments of the present invention and are not intended to limit the scope of the present invention. Without departing from the spirit of the present invention, all changes and improvements made by those skilled in the art to the technical solutions of the present invention should fall within the protection scope defined by the present invention.
Claims
1. A boron-containing polycyclic aromatic compound, characterized in that, The specific structure is shown below: 。 2. The boron-containing polycyclic aromatic compound according to claim 1, characterized in that, One or more of the hydrogen atoms bonded to C are replaced by deuterium atoms.
3. The application of the boron-containing polycyclic aromatic compound according to any one of claims 1 to 2 in the fabrication of organic electroluminescent devices.
4. An organic electroluminescent device, comprising a light-emitting layer, characterized in that, The raw materials for preparing the light-emitting layer include at least one of the boron-containing polycyclic aromatic compounds as described in any one of claims 1 to 2.
Citation Information
Patent Citations
Boron-containing organic compound as OLED doping material and organic light-emitting device
CN114315876A
KR20230033457A